2004
DOI: 10.1677/jme.0.0320257
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of hepatic genes, especially IGF-binding protein-1, correlating with serum corticosterone in microarray analysis

Abstract: Microarray technology was evaluated for usefulness in assessing relationships between serum corticosterone and hepatic gene expression. Nine pairs of female Swiss mice were chosen to provide a wide range of serum corticosterone ratios; cDNA microarray analysis (∼8000 genes) was performed on their livers. A statistical method based on calculation of 99% confidence intervals discovered 32 genes which varied significantly among the livers. Five of these ratios correlated significantly with serum corticosterone ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…Thus, an EB dependent increase in neuroprotective genes may contribute to maintenance of hippocampal function with age. Some aging-EB responsive genes have been linked to premature aging (Tbl2, Il13ra1), transcriptional changes in the hippocampus of senescence-accelerated mice (Dusp12) (Meng et al, 1998;Kyng et al, 2003;Cheng et al, 2007), and aging in different organisms (Lass2) (Obeid and Hannun, 2003), or organs (Peli1) (Cheng et al, 2004;Chelvarajan et al, 2006). Some genes may be associated with biological markers of aging including altered lipid/ cholesterol metabolism (Abca2, Vldlr, Acsl5, Srebf1, Apoa1) (Foster, 2006), lipid composition (Ptdss2) (Giusto et al, 2002), mitochondrial function (Atp5g1, Aco2) (Poon et al, 2006), and structural changes (Ctsb) (Bednarski et al, 1997).…”
Section: Treatment Effects On Transcription In the Aging Hippocampusmentioning
confidence: 99%
“…Thus, an EB dependent increase in neuroprotective genes may contribute to maintenance of hippocampal function with age. Some aging-EB responsive genes have been linked to premature aging (Tbl2, Il13ra1), transcriptional changes in the hippocampus of senescence-accelerated mice (Dusp12) (Meng et al, 1998;Kyng et al, 2003;Cheng et al, 2007), and aging in different organisms (Lass2) (Obeid and Hannun, 2003), or organs (Peli1) (Cheng et al, 2004;Chelvarajan et al, 2006). Some genes may be associated with biological markers of aging including altered lipid/ cholesterol metabolism (Abca2, Vldlr, Acsl5, Srebf1, Apoa1) (Foster, 2006), lipid composition (Ptdss2) (Giusto et al, 2002), mitochondrial function (Atp5g1, Aco2) (Poon et al, 2006), and structural changes (Ctsb) (Bednarski et al, 1997).…”
Section: Treatment Effects On Transcription In the Aging Hippocampusmentioning
confidence: 99%
“…46 It has been documented that local infusion of dexamethasone into the growth plate causes a local inhibition effect on longitudinal bone growth, 47 which might be mediated through local reduction of IGF-1 expression within the growth plate, 48 or by increasing expression of binding proteins. 12 Adding to the controversy, several of the larger studies have not found an independent effect of steroids on growth, especially with short-term or low-dose steroid treatment. 2,26,27,29 -30 Griffiths et al, 27 in the largest study published so far, found that the use of corticosteroids was associated with height retardation only after the first year of treatment, but this effect was not significant if corrected for disease severity.…”
Section: Drugsmentioning
confidence: 99%
“…IGFBP-1 expression is increased in states of insulopenia and starvation and by corticosteroids in a dose-dependent manner. 11,12 Factors that increase IGFBP-1 may decrease the availability of bioactive IGF-1.…”
mentioning
confidence: 99%
“…A few recent applications include microbe identification,[1] tumor classification,[2] evaluation of the host cell response to pathogens, and analysis of the endocrine system. [3] Microarrays opened up an entire new world to researchers. No longer is one restricted to studying a unique single aspect of the host/pathogen relationship; instead one can explore a genome-wide view of this complex interaction.…”
Section: Introductionmentioning
confidence: 99%